2021
DOI: 10.1038/s41440-021-00754-7
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-based ultrasound renal denervation in patients with resistant hypertension: the randomized, controlled REQUIRE trial

Abstract: Renal denervation is a promising new non-pharmacological treatment for resistant hypertension. However, there is a lack of data from Asian patients. The REQUIRE trial investigated the blood pressure-lowering efficacy of renal denervation in treated patients with resistant hypertension from Japan and South Korea. Adults with resistant hypertension (seated office blood pressure ≥150/90 mmHg and 24-hour ambulatory systolic blood pressure ≥140 mmHg) with suitable renal artery anatomy were randomized to ultrasound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 47 publications
2
63
0
Order By: Relevance
“…Surprisingly, this measure was not significantly different between the renal denervation (-6.6 mmHg) and the sham control (-6.5 mmHg) groups (mean difference: -0.1, [95% CI -5.5 to 5.3 mmHg]; p = 0.971). 37 However, the absolute change of the reduction from baseline in 24-hour ambulatory SBP in the renal denervation group was of a similar magnitude to decreases in the two previous prospectively-powered sham-controlled ultrasound-based RDN studies. 30,34 Similar to the SYMPLICITY HTN-3 trial, the key difference between the REQUIRE trial and these trials was the sizeable reduction from baseline in 24-hour ambulatory SBP in the sham group, approximately double that of its predecessors.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 63%
“…Surprisingly, this measure was not significantly different between the renal denervation (-6.6 mmHg) and the sham control (-6.5 mmHg) groups (mean difference: -0.1, [95% CI -5.5 to 5.3 mmHg]; p = 0.971). 37 However, the absolute change of the reduction from baseline in 24-hour ambulatory SBP in the renal denervation group was of a similar magnitude to decreases in the two previous prospectively-powered sham-controlled ultrasound-based RDN studies. 30,34 Similar to the SYMPLICITY HTN-3 trial, the key difference between the REQUIRE trial and these trials was the sizeable reduction from baseline in 24-hour ambulatory SBP in the sham group, approximately double that of its predecessors.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 63%
“…After 2 months follow-up, the results showed that the RDN group was better than the control group in lowering BP [−8.0 vs. −3.0 mmHg, mean difference: −4.5 mmHg (95% CI: −8.5 to −0.3, p = 0.022)]. However, satisfactory results were not obtained in the recently published REQUIRE study ( 56 ), which included 143 Korean and Japanese patients with refractory hypertension who were randomly assigned to the RDN based on Paradise system and sham group on the basis of antihypertensive medications. There was no significant difference in 24-h SBP change between the RDN and sham groups at 3-month follow-up (−6.6 vs. −6.5 mmHg, p = 0.971).…”
Section: Clinical Evidencementioning
confidence: 92%
“…In terms of evidence from Asia, the REnal denervation on Quality of 24‐hour BP control by Ultrasound In REsistant hypertension (REQUIRE) trial did not find any difference between the RDN and sham control group in the primary endpoint of 24‐hour SBP at 3‐month follow‐up after ultrasound RDN. 122 However, there were a number of potential reasons that contributed to these findings. For example, increased awareness of high BP may change adherence to medication or lifestyle modifications after randomization, especially in the control group.…”
Section: Other Considerationsmentioning
confidence: 99%